Evaluation of the pathogenicity potential, antimicrobial susceptibility and genomic relations of Yersinia enterocolitica strains from food and human origin - Lucero Estrada, Cecilia Stella Marys (2015)
Yersinia enterocolitica is a food-borne pathogen that causes gastroenteritis with occasional postinfection sequels. This study was aimed to determinate the pathogenic potential, antimicrobial susceptibility, and genomic relationships of Y. enterocolitica strains of different bioserotypes (B/O) isolated from foods and human samples in San Luis, Argentina. Strains obtained by culture were bioserotyped and characterized by phenotypic and genotypic virulence markers, antimicrobial susceptibility, and pulsed-field gel electrophoresis (PFGE). Yersinia enterocolitica was detected in 9.2% of 380 samples, with a distribution of 10.6% (30/284) for food products and 5.2% (5/96) for human samples. Regarding the pathogenic potential, B1A strains of different serotypes were virF– ail–, of which 72.0% (13/18) were ystB+ with virulence-related phenotypic characteristics. Among B2/O:9 isolates, 75.0% (9/12) exhibited the genotype virF+ ail+ ystB– along with phenotypic traits associated with virulence; the same genotype was observed in 80.0% (4/5) of B3/O:3 and B3/O:5 strains. By PFGE, it was possible to separate Y. enterocolitica biotypes into 4 clonal groups (A to D) with 23 genomic types, generating a discriminatory index of 0.96. All isolates were susceptible to antimicrobials used for clinical treatment. This study highlights the presence of pathogenic bioserotypes and the high genomic diversity of the Y. enterocolitica strains isolated in our region.